2023
DOI: 10.5851/kosfa.2022.e64
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Electrical Conductivity to Improve Prediction Accuracy of Cooking Loss of Pork Loin

Abstract: Ethics approval (IRB/IACUC) (This field may be published.) This article does not require IRB/IACUC approval because there are no human and animal participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Dependent variables sets: It is worth emphasising the higher value of the coefficient of canonical correlation (C R = 0.77 **) obtained by the cited authors between the set containing EC 2 and pH 24 and the set of traits characterising the value of culinary meat and including the measurement of the lightness of the color of the meat. Jo et al [48] confirmed that adding electrical conductivity as an explanatory variable can predict cooking loss of pork loin with minimally destructive measured quality parameters, except for moisture and protein content (highly correlated with cooking loss), which are difficult to rapidly and accurately analyze in an industrial conditions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dependent variables sets: It is worth emphasising the higher value of the coefficient of canonical correlation (C R = 0.77 **) obtained by the cited authors between the set containing EC 2 and pH 24 and the set of traits characterising the value of culinary meat and including the measurement of the lightness of the color of the meat. Jo et al [48] confirmed that adding electrical conductivity as an explanatory variable can predict cooking loss of pork loin with minimally destructive measured quality parameters, except for moisture and protein content (highly correlated with cooking loss), which are difficult to rapidly and accurately analyze in an industrial conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Jo et al [48] estimated the predictability of pork loin cooking losses using a rapid and minimally destructive method, showing that pH and protein content were significantly correlated with cooking losses. They used pH, CIE L *, CIE b *, moisture content and protein content as explanatory variables.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An activity of phosphate in meat products is a dissociation of actomyosin formed in the postmortem muscle [ 34 , 41 ]. High-pressure treatment improves the solubility of myofibrillar proteins by dissociating actomyosin [ 41 , 42 ].…”
Section: Replacement Of Synthetic Additivesmentioning
confidence: 99%
“…An activity of phosphate in meat products is a dissociation of actomyosin formed in the postmortem muscle [ 34 , 41 ]. High-pressure treatment improves the solubility of myofibrillar proteins by dissociating actomyosin [ 41 , 42 ]. Guan et al [ 42 ] reported that the stability of pork emulsions was improved when high-pressure processing and soy protein isolate hydrolysates were used.…”
Section: Replacement Of Synthetic Additivesmentioning
confidence: 99%